Peserta Didik dalam Pandangan Nativisme, Empirisme, dan Konvergensi - Anshory, Muhammad Isa; Murtadho, Imam; Nuryahya, Ikhsan (TSAQOFAH, 2025)
The theory of student development has become an important study in the world of education. Three main theories, namely nativism, empiricism, and convergence, offer different perspectives in understanding the factors that influence student learning and growth. Nativism emphasizes that individual development is more influenced by innate factors, while empiricism assumes that experience and environment are the main factors in learning. Convergence theory tries to combine these two views, by emphasizing the interaction between genetic and environmental factors in the educational process. This research aims to analyze the extent to which these three theories are still relevant in the context of modern education. Although convergence is becoming a more widely accepted approach, there is still a research gap regarding how innate and environmental factors interact specifically in the learning process, especially with current technological developments.